A study of leadership styles of female and male managers in 10 different nationality banks in Luxembourg, using the Personal Attributes Questionnaire and personal interviews - Cames, Isabelle (Cranfield University, 1997)
This thesis is concerned with the similarities and Merences between the leadership styles of female and male' managers in general, 'and their respective levels of Instrumentality and Expressiveness in particular. In view of the lack of research, involving managers of both sexes in real work settings and in non Anlgo-Saxon environments, the present research has been conducted in the multi-cultural environment of the Luxembourg banking sector, with female and male managers from 13 different countries. A total of 33 female and 33 male managers, working in 10 banks of different nationalities, completed the Personal Attributes Questionnaire (PAQ) and were interviewed. The objectives of the research were to measure and compare the perceived levels of Instrumental and Expressive traits, as well as to analyse the perceived leadership styles of the participating managers themselves, their superiors and successful managers in their respective banks. Individual case studies were used to clarify and compare the feminine, masculine and androgynous leadership styles of participating managers from the 3 main PAQ categories, in order to establish whether the *managers' descriptions of themselves are in line with their PAQ results. Finally, 3 banks were chosen to represent the highest, the median and the lowest scores of the banks' nationalities on Hofstede's Masculinity Index, in order to establish whether differences on leadership styles exist between the banks in accordance with Hofstede's research. The present thesis has shown female managers, to possess exceptionally high levels of Instrumental traits compared to the male managers of this study, as well to women and men from other studies. In addition, the leadership styles measured by the PAQ categories to which the participating managers belong, were found to be consistent with the leadership styles they attribute to themselves. Significant differences were established between the 3 different nationality banks, but not in accordance with Hofstede's findings.